2021
DOI: 10.1111/and.14156
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 vaccine hesitancy linked to increased internet search queries for side effects on fertility potential in the initial rollout phase following Emergency Use Authorization

Abstract: The Emergency Use Authorization (EUA) of the COVID‐19 vaccine on December 11, 2020 has been met with hesitancy for uptake with some citing potential impacts on future fertility. We hypothesised that irrespective of sex, fertility‐related queries would markedly increase during the 48 days following EUA of the coronavirus vaccine. We sought to objectively identify trends in internet search queries on public concerns regarding COVID‐19 vaccine side effects on fertility that might impact vaccine uptake. We used Go… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
59
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(62 citation statements)
references
References 17 publications
2
59
0
1
Order By: Relevance
“…Nevertheless, the vaccination pace in many countries is slower than expected, partially due to public fear of possible adverse effects and the potentially negative long-term effect of the vaccine (Lo Re et al, 2021). Despite no evidence of a negative effect on male or female fertility, as stressed by the Association of Reproductive and Clinical Scientists and the British Fertility Society (Web-1;Iacobucci, 2021), many people are still hesitant to receive the vaccine due to fertility concerns (Diaz et al, 2021). Hence, this study aimed to investigate the effect of the BNT162b2 COVID-19 vaccine on sperm parameters among men, including men with fertility issues and impaired initial sperm parameters; We hypothesized that the vaccine would not affect sperm quality.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the vaccination pace in many countries is slower than expected, partially due to public fear of possible adverse effects and the potentially negative long-term effect of the vaccine (Lo Re et al, 2021). Despite no evidence of a negative effect on male or female fertility, as stressed by the Association of Reproductive and Clinical Scientists and the British Fertility Society (Web-1;Iacobucci, 2021), many people are still hesitant to receive the vaccine due to fertility concerns (Diaz et al, 2021). Hence, this study aimed to investigate the effect of the BNT162b2 COVID-19 vaccine on sperm parameters among men, including men with fertility issues and impaired initial sperm parameters; We hypothesized that the vaccine would not affect sperm quality.…”
Section: Introductionmentioning
confidence: 99%
“…6 Recent reports show that fear regarding side effects, in particular regarding fertility implications, are driving these concerns. 8,9 This is fueled, in part, by high-profile individuals raising unfounded fears regarding the vaccine's safety with respect to fertility. 10 Our group in Miami published the first prospective study on the effects of the COVID-19 vaccine on sperm parameters.…”
Section: Male Fertility and Covid-19 Vaccinementioning
confidence: 99%
“…Recently, an increased concern regarding COVID-19 vaccine and fertility has been reported as major cause for hesitancy in vaccine uptake [ 103 ]. Although no study has demonstrated an impact of SARS-CoV-2 infection and COVID-19 vaccination on ovarian function [ 104 ] or on sperm parameters [ 105 ], counselling with patients should be undertaken to help mitigate these concerns.…”
Section: Prevention Of Covid-19 In Pregnant Women With Vaccinesmentioning
confidence: 99%